Hasil Belajar IPA Tentang Gerak Benda dan Energi dengan Penggunaan Alat Peraga pada Siswa Kelas III SDN 06 Dobo - Erwin, Moh. Erwin Budiana (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
Based on observation data, it can be seen that science learning in elementary schools still does not improve student learning outcomes. This is because the learning is still teacher-centered or learning that is centered on the teacher (the teacher is active while the students are passive) and the use of learning media is still lacking. This can cause the impression of boring learning and can result in low student motivation which has an impact on student learning outcomes in learning. Therefore, a study was conducted on the use of role-playing tools in improving science learning outcomes about the motion of objects and energy. The purpose of this study was to improve science learning outcomes about the motion of objects and energy by using teaching aids. This study used classroom action research (CAR). The research subjects were grade III students of SD Negeri 06 Dobo, Aru Islands Regency, Maluku. The results of the study showed that the use of role-playing tools can increase (1) student activity in learning, (2) increase teacher activity, (3) Improve student learning outcomes in science learning about the motion of objects and energy. Based on the results of the study, it can be concluded that the use of teaching aids can improve student learning outcomes in science learning about the motion of objects and energy. Suggestions that can be given in this study are that student learning outcomes can be improved through other learning methods and media.